Physiological attributes of soybean seeds submitted to artificial cooling (Research, Society and Development, 2020)
The present study aimed to evaluate the physiological attributes of soybean seeds submitted to artificial cooling prior to bagging. The research was carried out at the Seed Laboratory of the Federal Technological University of Paraná - UTFPR, located in the municipality of Dois Vizinhos - Paraná. Seeds from the soybean cultivars TMG 7262 RR and TMG 7063 IPRO were used, produced in the 2017/2018 harvest and processed at the Seed Processing Unit of the Cooperativa Agropecuária Tradição, in the region of Pato Branco - Paraná. At the time of beneficially the treatments were separated, in samples that passed the cooling (Cool Seed), or not cooled. The tests to check the physiological quality of soybean seeds were, germination, accelerated aging, length of area and root part, dry mass and fresh mass, and electrical conductivity. The experiment took place in a completely randomized design (DIC), with four replications. Since the data set was subjected to the normality and homogeneity test, and after the assumptions were satisfied, the data were subjected to analysis of variance (Anova). If there was significance between the treatments, with the aid of the Genes statistical program, the test of means comparison test (Tukey at 5% probability) was used. Thus, it is concluded that artificially cooled soybean seeds have higher physiological potential than uncooled seeds. However, for seed lots of high physiological quality, this higher performance may not be observed.